Long term gamma-ray variability of blazars - Bhoomika Rajput; C. S. Stalin; Suvendu Rakshit (EDP SCIENCES S A, 2025)
We used the data from the Fermi Gamma-ray Space Telescope to characterise the gamma-ray flux variability of blazars on month-like time scales. Our sample consists of 1120 blazars of which 481 are flat spectrum radio quasars (FSRQs) and 639 are BL Lac objects (BL Lacs). We generated monthly binned light curves of our sample for a period of approximately nine years from 2008 August to 2017 December and quantified variability by using excess variance (F-var). On month-like time scales, 371/481 FSRQs are variable (80%), while only about 50% (304/639) of BL Lacs are variable. This suggests that FSRQs are more variable than BL Lac objects. We find a mean F-var of 0.55 +/- 0.33 and 0.47 +/- 0.29 for FSRQs and BL Lacs respectively. Large F-var in FSRQs is also confirmed from the analysis of the ensemble structure function. By Dividing our sample of blazars based on the position of the synchrotron peak in their broad-band spectral energy distribution, we find that the low synchrotron peaked (LSP) sources have the largest mean F-var value of 0.54 +/- 0.32 while the intermediate synchrotron peaked (ISP) and high synchrotron peaked sources have mean F-var values of 0.45 +/- 0.25 and 0.47 +/- 0.33 respectively. On month-like time scales, we find FSRQs to show a high duty cycle (DC) of variability of 66% relative to BL Lacs that show a DC of 36%. We find that both the F-var and time scale of variability (tau) do not correlate with M-BH. We note that F-var is found to be weakly correlated with Doppler factor (delta) and tau is also weakly correlated with delta. Most of the sources in our sample have tau of the order of days, which might be related to processes in the jet. We find marginal difference in the distribution of tau between FSRQs and BL Lacs.